2016
DOI: 10.1007/s12275-016-5555-4
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Interferon-mediated antiviral activities of Angelica tenuissima Nakai and its active components

Abstract: Angelica tenuissima Nakai is a widely used commodity in traditional medicine. Nevertheless, no study has been conducted on the antiviral and immune-modulatory properties of an aqueous extract of Angelica tenuissima Nakai. In the present study, we evaluated the antiviral activities and the mechanism of action of an aqueous extract of Angelica tenuissima Nakai both in vitro and in vivo. In vitro, an effective dose of Angelica tenuissima Nakai markedly inhibited the replication of Influenza A virus (PR8), Vesicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…tenuissima ) is one of the traditional Asian medicines that has been used to treat headaches, diarrhea, epilepsy, rheumatic arthritis, and gynecological diseases and anemia for women [ 9 ]. Recently, it has been demonstrated to have various anti-viral, anti-osteoporosis, and anti-inflammatory effects [ 10 , 11 , 12 ]. In our previous study, it was confirmed that fermented A. tenuissima root (FAT) had an anti-melanogenetic effect, and we found that the content of ligustilide, and one of the active compounds, was higher during fermentation by Aspergillus oryzae [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…tenuissima ) is one of the traditional Asian medicines that has been used to treat headaches, diarrhea, epilepsy, rheumatic arthritis, and gynecological diseases and anemia for women [ 9 ]. Recently, it has been demonstrated to have various anti-viral, anti-osteoporosis, and anti-inflammatory effects [ 10 , 11 , 12 ]. In our previous study, it was confirmed that fermented A. tenuissima root (FAT) had an anti-melanogenetic effect, and we found that the content of ligustilide, and one of the active compounds, was higher during fermentation by Aspergillus oryzae [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phellodendron, Coptis, Scutellaria, Gardenia, Sanguisorba, Atractylodes, Angelica, Paeonia, Saussurea and Chinese Licorice have both antiviral and anti-bacterial effects. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Pinellia, Paeonia, Astragalus, Dioscorea, and Aurantium have antibacterial activity. [29][30][31][32][33][34][35][36][37][38][39] All herbs in this Chinese medicine formula with the exception of Phellodendron and Pinellia help alleviate pain (Table 2).…”
mentioning
confidence: 99%